Kelayakan Aplikasi Pengaduan Berbasis Android dalam Pencegahan Bahaya Psikososial Bagian Jurnalistik Perusahaan Media X - Raja Alma Dwi Mayasari; Evi Widowati (Jurnal Health Sains, 2021)
The psychosocial hazard level of journalists job stres is quite high, reaching 51.63% of workers experiencing work-related stres with losses of up to $300 billion each year due to stres at work, then the number of complaints reported to Dewan Pers reaches over 500 cases with the percentage of android users in Indonesia amounted to 90.64%. In Media Company X Semarang City was found that 10 journalists (66.7%) experienced moderate work stres and 5 journalists (33.3%) experienced heavy work stres. The aim of this study was to compile and assess the feasibility of developing an android-based complaint application development product in the prevent of psychosocial hazards journalism in Media Company X Semarang City. The results of this research was android-based application products. The developed product was declared feasible to use based on the assessment of media experts 82.7% and material experts 80.7%, assessment of usability worker response 76.6%. It can be concluded that this android-based complaint media is good and feasible to be applied as a media to prevent psychosocial hazards journalism in Media Company X Semarang City. This research used Research and Development (R&D). The assessment of the feasibility of the application was carried out by 4 validators specifically 2 media expert and 2 material expert. The informants in the research consist into 22 main informants and 2 supporting informants. The data collection used human instrument, interview guidelines, and questionnaire. The data were analyzed with a description of the content, the data were presented in narrative and table form.